STATE OF DIGITALIZATION OF EDUCATION IN THE CONTEXT OF OPEN SCIENCE - Shyshkina, Mariya; Nosenko, Yuliya; Marienko, Maiia (Physical and Mathematical Education, 2022)
Formulation of the problem. Today, many developed countries are at the stage of introducing the principles of open education. There are a number of obstacles on the way to the introduction of open science. Identifying these obstacles is important for developing appropriate policies and recommendations aimed at eliminating them and strengthening driving factors. The design and implementation of cloud-oriented systems of open science is determined by the goal of ensuring both high productivity and ease of use not only by scientific communities, but also in education and professional development of teachers.Materials and methods. The goal of the article was solved thanks to the use of the following theoretical methods of scientific research: analysis of scientific research (current state, in particular foreign experience), comparison of domestic and foreign experience, the method of ascent from the abstract to the concrete.Results. The role of digitization in achieving the goals of open science is revealed. The general principles of open science are defined. The three "Whales" of open science (open access to scientific publications, open research data, open collaboration) are described and methods of their implementation are presented. The key aspects touched by open science are shown. The contents of four open scientific practices are revealed. The relationship between open science and open education is shown. The problems that exist within the scope of this topic are outlined. The prospects of digitization of education in the context of open science are determined. Factors identified for more effective development of open science in Ukraine.Conclusions. It is foreseen that as a result of the introduction of the principles of open science, Ukraine will receive a number of advantages. Taking into account the modern trends of the European space of open science, using the advantages of cloud-oriented services of open science in scientific and educational activities will contribute to the improvement of its quality and efficiency, the wider use of services of open science, and the increase in the level of training of education personnel.
Keywords: digitization; open science; digitization of education; digital technologies; principles of open science